Control of public money the fiscal machinery in developing countries - Premchand, A (New Delhi Oxford University Press, 2000)
This book provides an integrated analysis of the fiscal machinery within the executive wing,the audit agency,and the legislature and partnerships with the private sector.The book outline the objective of fiscal policy and explores how the system achieves
Keywords: India-Economic policy; Fiscal policy-India; Budget-India